A preliminary study on the effect of Artemisia vulgaris L. leaf extract on the larvae and subsequent stages of drosophila malanogaster L. - Suguilon, Sharon Samodal
First instar larvae were sprayed with 10, 15 and 25 concentrations each of both aqueous and ethanol extract. Mortality counts were made after 24 hours and subsequent changes and mortalities in the remaining insects were observed until the emergence of the adult. Results showed increase in mortality with increasing extract concentration. Ethanol extract resulted in higher mortality compared with the aqueous extract. Additional mortalities were observed beyond 24 hours. Not all of the remaining larvae which pupated survived to become adults. This resulted in lower number of adults that emerged. Abnormality was observed in one emerged adult in the form of reduced or vestigial wing. (p)Inhibition of emergence by causing mortalities to the larvae and subsequent stages are the characteristic features of growth regulators. The study indicates that A. vulgaris extract has insecticidal as well as insect growth regulating properties and thus, has a potential to be a controlling agent of D. melanogaster.